The Grammatical Blunders of Qurʾān Reciters: Zallat al-qāriʾ by Abū Ḥafṣ al-Nasafī (d. 537/1142) - Nasser, Shady Hekmat (Journal of Abbasid Studies, 2015)
Jurists require Muslims to acquire a basic level of literacy in order to recite the Qurʾān during ritual prayers. For the educated elites, scholars, and in particular leaders of congregational prayers (imām), the expectation is the correct articulation of Arabic letters and adherence to grammatical rules. To that end, Ḥanafī jurists have developed some regulations, which attempt to identify the errors one may or may not commit during ritual prayers. These regulations are called Zallat al-qāriʾ, namely, the grammatical blunders of Qurʾān reciters. Zallat al-qāriʾ identifies these errors and distinguishes between those that would invalidate prayer and those that would not. In this article, I discuss whether a solecist (lāḥin/laḥḥān) was considered eligible to become imām and lead congregational prayers. I then discuss the subject of Zallat al-qāriʾ and its theological implications for understanding the nature of the Qurʾān and its composition (naẓm). Finally, I conclude with an edition of a treatise by Abū Ḥafṣ al-Nasafī (d. 537/1142) titled Zallat al-qāriʾ and a summary of its contents.